Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa Kelas IX SMP Angkasa Kupang Pada Materi Kesebangunan dan Kekongruenan Berbantuan E-book Interaktif - Bees, Yumitro Aretwin; Samo, Damianus D.; Nubatonis, Ofirenty Elyada (Universitas Nusa Cendana, 2023)
This research was motivated by the mathematics learning results of class IX students at Angkasa Kupang Middle School, especially in the material of congruence and congruence which were still low. The aim of this research is to improve the learning outcomes of class IX students at SMP Angkasa Kupang on congruency and congruence material. The type of research used is Classroom Action Research (PTK) which refers to the Kemmis & Mc Taggart model, which is carried out in 2 cycles with each cycle consisting of 4 stages, namely: 1) Planning; 2) Implementation; 3) Observation; and 4) Reflection. The data collection techniques in this research are observation and tests, while the data analysis is descriptive qualitative and quantitative. The results of this research show that the learning outcomes in cycle I were 55,55%, increasing to 81,48% in cycle II, the value of implementing observations of teacher teaching activities in cycle I was 93,17% increasing to 100% in cycle II and the value of implementing activities students in cycle I was 76,92%, increasing to 96,15% in cycle II. Thus, it can be concluded that the application of the problem based learning model assisted by interactive e-books can improve the learning outcomes of class IX students at SMP Angkasa Kupang on congruence and congruence material. Keywords: interactive e-book, learning outcomes, problem based learning, similarity and congruence